Hubungan Kemampuan Pemecahan Masalah dengan Hasil Belajar Matematika Kelas IV SDN 27 Kota Padang - Sagita, Yora; Zainil, Melva; Zuryanty, Zuryanty (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
The purpose of this research is to know correlations between problem-solving ability with mathematics learning result for 4th grade students at public elementary school 27 in Padang city for the 2017/2018 academic year. The type of this research is correlations. The population of the research is all 4th grade students of SD N 27 Sungai Sapih was 42 students, then 21 students as sample. The data analysis using simple linear regression analysis. the research result shows that correlation coefficient of 0,7036. in interval 0,70 ≤ r > 0,90 with a degree of strong or high corrrelations. It means 0,7036 have a strong or high  correlations. Then the result of significant correlation coefficient with α = 0,05 showed  and . Because . It means that  is accepted.Keywords: Problem Solving Ability; Learning Result.